Estimating the optimal number of samples to determine the effective population size in livestock - Manunza, Arianna; Cozzi, Paolo; Boettcher, Paul; Curik, Ino; Looft, Christian; Colli, Licia; Sölkner, Johann; Mészáros, Gábor; Stella, Alessandra (Frontiers in Genetics, 2025)
Effective population size (Ne) is a key parameter in various biological disciplines, including evolutionary biology, conservation genetics, and livestock breeding programs. When applying genomic approaches to estimate Ne or other indicators of genetic variation, sample size is among the critical factors that directly affect the balance between cost and precision. In this study, we investigated the impact of sample size on Ne estimates by analyzing data from previous genotyping studies and simulations. Our results suggest that a sample size of 50 animals is a reasonable approximation of the “true” (“unbiased”) Ne value within the populations analyzed. While estimating the Ne value is an important starting point in population genetics, additional factors, such as the degree of inbreeding, population structure, and admixture, must be taken into account to obtain a comprehensive genetic evaluation and avoid misinterpretation. We conclude that linkage disequilibrium (LD)-based approaches are well suited for the estimation of Ne in livestock populations. However, careful interpretation of results is essential as current bioinformatics tools may introduce potential biases due to methodological assumptions, marker density, or population-specific factors.